Sobrevivência de ninhos e novos aspectos da biologia reprodutiva de aves para o Centro de Endemismo Pernambuco - Araújo, Lahert William Lobo de (Universidade Federal de São Carlos, 2024)
Tropical forests are megadiverse, but at the same time they have been highly degraded in such a way that biodiversity conservation has often relied on the management of the remaining forest patches. The survival of bird’s nests can be low in fragmented habitats due to top-predators extinction causing increased population densities of small and medium-sized nest predators, or because of the invasion of alien nest predators. Large forest tracts no longer exist in the Pernambuco Endemism Center (PEC) and all of the top-predators were long extinct. Here, we addressed nest survival of forest understory birds from three PEC fragments (690, 979, and 1049 ha), and we used infra-red camera-traps for predators’ identification. Apparent nest survival was 15.5%, and nest-day based survival probability for the four more representative species (including two endemic and threatened taxa) were 2.6, 4.4, 6.9, and 18.9%. Predators were marmosets (25%), opossums (25%), tegu (19.4%), coati (16.7%), snakes (8.3%) and hawks (5.5%). Furthermore, we present nest descriptions and new reproductive information for the brown-winged mourner Schiffornis turdina intermedia and for the tody-tyrant Hemitriccus griseipectus naumburgae, as well as the first description of the pre-copulatory display of the reddish hermite Phaetornis ruber. Our data improved our understanding about the main threats to the birds of the PEC and provided a background for the development of conservation management strategies.
Nest survival and new aspects of bird reproductive biology for the Pernambuco Endemism Center
Keywords: Predação de ninhos; Florestas tropicais; Mata Atlântica; câmeras-trap; Comportamento de nidificação; Nest predation; Tropical forests; Atlantic Forest; Camera-traps; Nesting behaviour; CIENCIAS BIOLOGICAS::ECOLOGIA